Comparing terrestrial laser scanners' ability to measure tree height and diameter in a managed forest environment. Issue 3 (2nd July 2020) - Brack, C.; Schaefer, M.; Jovanovic, T.; Crawford, D.
ABSTRACT: Terrestrial laser scanning (TLS) instruments like the Zebedee (including the Zeb-1 and its derivatives) and Dual-Wavelength Echidna LiDAR (DWEL) can usefully measure tree diameter, height and annual height growth for trees up to at least 10 m tall in a forest plantation setting. In a case study at the National Arboretum Canberra, these two types of scanner were compared with traditional methods (diameter tape and height stick) in the measurement of tree diameter, height and growth rate. The TLS instruments were accurate with height measurement correlations of not different to 1:1 and with r 2 = 0.99 and 0.98 (Zeb-1 and DWEL, respectively), whereas comparing measurements of height growth over a two-year period, the TLS instruments displayed an agreement of 83% and 93%, respectively. The Zebedee instruments also correlated significantly with diameter at breast height (DBH; r 2 = 0.97), although limited tests with the DWEL collected at a single point in inventory plots did not find a significant correlation. The additional detail provided by TLS instruments such as Zeb-1and DWEL has the potential to substantially improve data collected about the spatial distribution, canopy dimensions and trunk parameters of numerous trees in an operational inventory of a forest stand. However, there may be difficulties in developing and testing new reference definitions of these parameters, especially 'diameter', that would allow historical comparisons and improved future use for foresters and ecologists.